Trends in the design and use of elastin-like recombinamers as biomaterials - Ibáñez-Fonseca, Arturo ; 0000-0002-2223-5041; Flora, Tatjana; Acosta, Sergio; Rodríguez-Cabello, José Carlos (Matrix Biology, 2019)
Elastin-like recombinamers (ELRs), which derive from one of the repetitive domains found in natural elastin, have been intensively studied in the last few years from several points of view. In this mini review, we discuss all the recent works related to the investigation of ELRs, starting with those that define these polypeptides as model intrinsically disordered proteins or regions (IDPs or IDRs) and its relevance for some biomedical applications. Furthermore, we summarize the current knowledge on the development of drug, vaccine and gene delivery systems based on ELRs, while also emphasizing the use of ELR-based hydrogels in tissue engineering and regenerative medicine (TERM). Finally, we show different studies that explore applications in other fields, and several examples that describe biomaterial blends in which ELRs have a key role. This review aims to give an overview of the recent advances regarding ELRs and to encourage further investigation of their properties and applications.
Copyright © 2019 International Society of Matrix Biology. Published by Elsevier B.V. All rights reserved.
Keywords: Biocompatible Materials/chemical synthesis; Elastin/chemistry; Gene Transfer Techniques; Humans; Hydrogels/chemistry; Intrinsically Disordered Proteins/chemistry; Peptides/chemical synthesis; Protein Domains; Regenerative Medicine; Tissue Engineering